Signal Transduction for TNFα-Induced Type II SOCS Expression and Its Functional Implication in Growth Hormone Resistance in Carp Hepatocytes - Jiang, Xue; He, Mulan; Bai, Jin; Chan, Chi Bun; Wong, Anderson O. L. (Frontiers in Endocrinology, 2020)
In mammals, local production of tumor necrosis factor α (TNFα) inhibits growth hormone (GH)-induced IGF-I expression at tissue level and contributes to GH resistance caused by sepsis/endotoxemia and inflammation. Although the loss of GH responsiveness can be associated with parallel rise in SOCS expression, the signaling mechanisms for TNFα-induced SOCS expression at the hepatic level have not been characterized and the comparative aspects of the phenomenon, especially in lower vertebrates, are still unknown. Recently, type II SOCS, including SOCS1-3 and CISH, have been cloned in grass carp and shown to act as the feedback repressors for GH signaling via JAK2/STAT5 pathway. To shed light on the mechanisms for TNFα-induced GH resistance in fish model, grass carp TNFα was cloned and confirmed to be a single-copy gene expressed in various tissues including the liver. In carp hepatocytes, incubation with the endotoxin LPS induced TNFα expression with parallel rises in SOCS1-3 and CISH mRNA levels. Similar to LPS, TNFα treatment could block GH-induced IGF-I/-II mRNA expression and elevate SOCS1, SOCS3 and CISH transcript levels. However, TNFα was not effective in altering SOCS2 expression. In parallel experiment, LPS blockade of IGF-I/-II signals caused by GH could be partially reverted by TNF receptor antagonism. At hepatocyte level, TNFα induction also triggered rapid phosphorylation of IkBα, MEK1/2, ERK1/2, MKK3/6, P38 MAPK, Akt, JAK2 and STAT1,3,5, and TNFα-induced SOCS1, SOCS3 and CISH mRNA expression could be negated by inhibiting the IKK/NFkB, MAPK, PI3K/Akt and JAK/STAT cascades. Our findings, as a whole, suggest that local production of TNFα may interfere with IGF-I/-II induction by GH in the carp liver by up-regulation of SOCS1, SOCS3 and CISH via IKK/NFB, MAPK, PI3K/Akt and JAK/STAT-dependent mechanisms, which may contribute to GH resistance induced by endotoxin in carp species.